«Я мушу продовжувати свою справу літописця…»: Гулагівська «одіссея» Надії Суровцової 1927–1954 рр. у реабілітаційно-мемуарному контексті - Рубльов, О.; Синицький, П. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2007)
The purpose of present article is the analysis of one of the early «cases» against the representatives of Ukrainian intellectuals of the USSR, faked by the republican GPU — the so-called «case of Surovtsova–Petrenko» 1927–1928. In the centre of attention is, an outstanding representative of literary and artistic intellectuals of Ukraine, historian and public figure Nadiya Surovtsova (1896–1985).